Laparoscopic Nissen (total) versus anterior 180° fundoplication for gastro-esophageal reflux disease: A meta-analysis and systematic review. Issue 37 (September 2017) - Du, Xing; Wu, Ji-Min; Hu, Zhi-Wei; Wang, Feng; Wang, Zhong-Gao; Zhang, Chao; Yan, Chao; Chen, Mei-Ping
Abstract: Background: Laparoscopic Nissen fundoplication (LNF) has been the gold standard for the surgical management of Gastro-esophageal reflux disease (GERD). Laparoscopic anterior 180° fundoplication (180° LAF) is reported to reduce the incidence of postoperative complications while obtaining similar control of reflux. The present meta-analysis was conducted to confirm the value of the 2 techniques. Methods: PubMed, Medline, Embase, Cochrane Library, Springerlink, and China National Knowledge Infrastructure Platform databases were searched for randomized controlled trials (RCTs) comparing LNF and 180° LAF. Data regarding the benefits and adverse results of 2 techniques were extracted and compared using a meta-analysis. Results: Six eligible RCTs comparing LNF (n = 266) and 180° LAF (n = 265) were identified. There were no significant differences between LNF and 180° LAF with regard to operating time, perioperative complications, length of hospital stay, patient satisfaction, willingness to undergo surgery again, quality of life, postoperative heartburn, proton pump inhibitor (PPI) use, postoperative DeMeester scores, postoperative lower esophageal sphincter (LES) pressure, postoperative gas-bloating, unable to belch, diarrhea, or overall reoperation. LNF was associated with a higher prevalence of postoperative dysphagia compared with 180° LAF, while 180° LAF was followed by more reoperation for recurrent reflux symptoms. Conclusion: LNF and 180° LAF are equally effective in controlling reflux symptoms and obtain a comparable prevalence of patient satisfaction. 180° LAF can reduce the incidence of postoperative dysphagia while this is offset by a higher risk of reoperation for recurrent symptoms. The risk of recurrent symptoms should need to be balanced against the risk of dysphagia when surgeons choose surgical procedures for each individual with GERD.